2020
DOI: 10.21203/rs.2.19868/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serum choline is associated with hepatocellular carcinoma survival: a prospective cohort study

Abstract: Background: Higher choline/betaine levels have been linked to lower risk of liver cancer, whereas existing data in relation to hepatocellular carcinoma (HCC) prognosis are scarce. Our objective was to examine the associations of the serum choline and betaine with HCC survival. Methods: 866 newly diagnosed HCC patients were enrolled in the Guangdong Liver Cancer Cohort. Serum choline and betaine were assessed using high-performance liquid chromatography with online electro-spray ionization tandem mass spectrome… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…27 Choline is an essential nutrient in all cells to maintain the stability of cell membrane structure, 28 and higher plasma Choline levels were associated with better HCC survival rates. 29 Choline of HCC plasma was lower than liver cirrhosis and healthy control group, 11 which is consistent with our results. L-Pyroglutamic acid is also called 5-oxoproline, a synthetic substrate of glutathione (GSH); its reduction will weaken hepatic antioxidant capacity.…”
Section: Discussionsupporting
confidence: 90%
“…27 Choline is an essential nutrient in all cells to maintain the stability of cell membrane structure, 28 and higher plasma Choline levels were associated with better HCC survival rates. 29 Choline of HCC plasma was lower than liver cirrhosis and healthy control group, 11 which is consistent with our results. L-Pyroglutamic acid is also called 5-oxoproline, a synthetic substrate of glutathione (GSH); its reduction will weaken hepatic antioxidant capacity.…”
Section: Discussionsupporting
confidence: 90%
“…[139][140][141][142] Choline depletion affects lipid metabolism and transport. 143 Jiang et al found that choline supplementation increases global DNA methylation and the expression of peroxisomal acyl-coenzyme A oxidase 1, which mediates FA β-oxidation. 144 Liu et al showed that higher choline intake can improve the overall general health.…”
Section: Methionine Metabolism and Cldsmentioning
confidence: 99%
“…The apparatus was used for the rapid quantification of the blood-borne metabolite choline in human plasma (physiological range 7 -20 µM [23]). Elevated concentrations of choline have been associated with several conditions including cardiovascular disease [24] and cancer [25]. We demonstrate that the hybrid device can perform multiple measurements with a LOD of 3.2 µM and resolution of 1.6 µM.…”
Section: Micromolar Metabolite Measurement In Anmentioning
confidence: 95%